ANALISIS FAKTOR PENYEBAB KESULITAN BELAJAR MATEMATIKA DI KELAS VII MTS MUHAMMADIYAH TANJUNG AMPALU - Suci Oktavia; M. Imamuddin; Noni Syafira; Fauzia Rahmi; Muhammad Iqbal (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to explain the factors that cause students' learning difficulties in mathematics. This research was conducted since October 2022 where research was conducted at MTs Muhammadiyah Tanjung Ampalu. The method used in this study is qualitative by conducting observations and interviews to obtain research results. The subjects of this study were several students and one teacher in the field of mathematics. the instrument used in this study was observation or observation and by conducting interviews with teachers and students. The results of this study indicate that students' learning difficulties in mathematics are caused by two factors, namely internal factors and external factors. Which internal factors are factors that come from within itself such as: 1). Student attitude, 2). Interest in learning, 3). Motivation to learn while the external factors come from outside the students where these factors are: 1). Learning strategy, 2). Learning tools, 3). Family Environment, and 4). Community environment. Where the internal factors and external factors can cause students' learning difficulties in mathematics. Keywords: Mathematics, factors, learning difficulties